A composite electrode for constructing a gradient pore structure alloy catalyst based on electrochemical dealloying and a preparation method thereof

CN123017999APending Publication Date: 2026-10-30INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611219743.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]针对现有碳毡电极结构均质、难以同时满足高效传质和高比表面积要求的问题,本发明提供一种基于电化学脱合金化构筑梯度孔结构合金催化剂的复合电极及其制备方法

Benefits of technology

1、通过多层合金成分梯度设计,利用脱合金过程中溶解速率差异在碳毡表面形成孔径梯度变化的多孔合金催化剂层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017999A_ABST
    Figure CN123017999A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of liquid flow battery electrode materials, and particularly relates to a composite electrode based on electrochemical dealloying for constructing a gradient pore structure alloy catalyst and a preparation method thereof. The method first performs pretreatment on a carbon felt substrate to introduce oxygen-containing functional groups, then sequentially deposits multiple alloy layers with different contents of sacrificial components on the surface of carbon fibers through step-by-step electrochemical deposition, and then performs one-step or step-by-step dealloying treatment, so that the different selective dissolution rates caused by the differences in the contents of the sacrificial components in the layers are utilized to form an alloy catalyst layer with a gradient pore structure in which the pore diameters gradually decrease in the thickness direction of the electrode. By adjusting the alloy composition, deposition parameters and dealloying conditions of each layer, the top layer pore diameter, bottom layer pore diameter, gradient layer thickness and pore diameter change gradient of the gradient pores can be precisely controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flow battery electrode material technology, specifically a composite electrode based on electrochemical dealloying to construct a gradient pore structure alloy catalyst and its preparation method. Background Technology

[0002] As an important large-scale energy storage technology, flow batteries have shown broad application prospects in fields such as smooth output of renewable energy grid connection, grid peak and frequency regulation, and distributed energy storage, thanks to their outstanding advantages of high safety, long cycle life, and independent design of power and capacity. Currently, the relatively mature all-vanadium redox flow battery has entered the commercial demonstration stage, while iron-chromium redox flow batteries, all-iron redox flow batteries, and zinc-based redox flow batteries have become research and development hotspots due to their potential advantages in resource cost, environmental friendliness, or energy density.

[0003] However, the overall performance and commercialization of this technology are largely constrained by electrode materials. Electrodes are the core site of electrochemical reactions, and their performance directly determines the kinetic rate of redox reactions of active materials (such as vanadium ions, iron ions, and bromide ions), thus affecting the battery's energy efficiency, power density, and cycle stability. Currently widely used three-dimensional porous carbon felt or graphite felt electrodes, while possessing excellent conductivity, chemical stability, and cost advantages, generally exhibit low intrinsic catalytic activity, leading to high overpotentials and slow kinetics in key electrochemical reactions. This problem has become one of the main bottlenecks in improving flow battery efficiency and reducing system operating costs. Therefore, effective surface modification and catalytic modification of carbon-based electrodes to significantly increase the number of active sites, optimize electronic structure, and improve surface wettability is a key research direction for overcoming this technological bottleneck. Developing novel electrode materials that combine high catalytic activity, excellent long-term stability, and good economic efficiency is crucial for promoting the large-scale application of flow battery technology.

[0004] However, traditional methods such as template methods and phase separation methods are difficult to achieve the above effects in carbon felt electrodes. Although laser processing technology can control the structure through power gradient scanning, the equipment cost is high and it is difficult to achieve uniform modification inside complex three-dimensional structures. Summary of the Invention

[0005] To address the problem that existing carbon felt electrodes have homogeneous structures and cannot simultaneously meet the requirements of efficient mass transfer and high specific surface area, this invention provides a composite electrode based on electrochemical dealloying to construct a gradient-pore alloy catalyst and its preparation method. This method involves sequentially depositing multilayer alloys with different sacrificial component contents on the surface of carbon fibers using a stepwise electrochemical deposition method. Then, by utilizing the difference in dissolution rates of each layer during the dealloying process, a porous alloy catalyst layer structure with gradient pore size is formed in situ along the thickness direction on the surface of the carbon felt electrode.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a composite electrode of an alloy catalyst with a gradient pore structure based on electrochemical dealloying includes the following steps: a carbon felt substrate is first treated with acid to introduce oxygen-containing functional groups, and then at least two alloy layers are sequentially deposited on the surface. Each alloy layer contains a catalytically active component and a sacrificial component, and the content of the sacrificial component in each alloy layer is different. Then, a dealloying treatment is performed to remove the sacrificial component in each alloy layer, thereby forming an alloy catalyst layer with a gradient pore structure in situ along the thickness direction on the surface of the carbon felt substrate, resulting in a composite electrode with an alloy catalyst layer with a gradient pore structure on the surface.

[0007] Carbon felt substrates include polyacrylonitrile-based carbon felt, pitch-based graphite felt, adhesive-based carbon felt, or carbon paper.

[0008] The acid treatment includes the following steps: the carbon felt substrate is ultrasonically degreased in acetone, ethanol, and deionized water for 10-30 minutes in sequence, then immersed in 5wt%-30wt% HNO3 or H2SO4 solution at 60℃-90℃ for 1-6 hours to introduce oxygen-containing functional groups, washed with deionized water until neutral, and then dried at 60℃-100℃ for 6-12 hours.

[0009] Depositing an alloy layer on a carbon felt substrate surface includes the following: At least two alloy layers are sequentially deposited on the surface of a carbon felt substrate using a stepwise electrochemical deposition method. The catalytic active components of each alloy layer are independently selected from one or more of Ni, Co, Cu, Fe, Bi, In, and Sb; the sacrificial components of each alloy layer are independently selected from one or more of Zn, Al, and Mg.

[0010] The total atomic percentage of the catalytically active component in each alloy layer is 20%~80%, and the total atomic percentage of the sacrificial component is 20%~80%. The content of the sacrificial component decreases or increases layer by layer from the innermost layer to the outermost layer of the deposited alloy layer. The difference in the content of the sacrificial component between adjacent layers is 10%~50%. The number of layers is 2~5, and the thickness of each layer is 0.2μm~2μm.

[0011] During the deposition of each alloy layer, the electrolyte is a metal ion salt solution containing catalytically active components and sacrificial components, with a total metal ion concentration of 0.05 mol / L to 0.5 mol / L, a deposition potential of -1.5 V to -0.5 V vs. SCE (relative to a saturated calomel electrode), a deposition time of 5 to 30 minutes, and a deposition temperature of 25℃ to 50℃.

[0012] During the deposition of each alloy layer, the content of the sacrificial component in the alloy layer is controlled by adjusting the concentration ratio of the sacrificial component to the catalytically active component in the electrolyte. The higher the concentration ratio, the higher the content of the sacrificial component.

[0013] The dealloying process includes the following: Electrochemical methods can be used to selectively dissolve sacrificial components in each alloy layer in an acidic medium. One-step dealloying can be used, taking advantage of the differences in the content of sacrificial components in each layer to naturally form a gradient pore structure; or stepwise dealloying can be used, by adjusting the dealloying potential or time at different dealloying stages to further enhance the pore size gradient.

[0014] The dealloying process is performed using either a potentiostatic method or a galvanostatic method. The potentiostatic method uses a potential range of -0.2V to 0.5V vs. SCE, with a processing time of 10 to 120 minutes. The galvanostatic method uses a current density of 1 mA / cm². 2 ~20mA / cm 2 The treatment time is 10-120 minutes. The acidic corrosive medium is a 0.1 mol / L to 2.0 mol / L solution of H2SO4, HCl, or HNO3.

[0015] The pore size of the gradient pores in each alloy layer is controlled by adjusting the sacrificial component content, including the innermost and outermost pore sizes. Higher sacrificial component content results in larger pore sizes after dealloying. The maximum pore size corresponds to 50nm~200nm when the sacrificial component content is highest, and the minimum pore size corresponds to 1nm~50nm when the sacrificial component content is lowest. The gradient pore structure exhibits a continuous or stepped change in pore size along the electrode thickness direction. Preferably, the surface layer is dominated by large pores to facilitate mass transfer, while the bottom layer is dominated by small pores to provide a high specific surface area. The total thickness of the alloy layers is 0.5μm~5μm; the pore size gradient is controlled by adjusting the number of alloy layers and the difference in sacrificial component content between layers.

[0016] During the dealloying process, inert gas is introduced for stirring or ultrasonic assistance, with a gas flow rate of 10 mL / min to 100 mL / min and an ultrasonic power of 50 W to 300 W. After dealloying, the electrode is rinsed repeatedly with deionized water or ethanol 3 to 5 times and dried in a vacuum drying oven at 60℃ to 100℃ for 6 to 12 hours to obtain a composite electrode with an alloy catalyst layer having a gradient pore structure on its surface.

[0017] The composite electrode with a loaded gradient pore structure alloy catalyst layer prepared by the above method can be used as a flow battery electrode. This electrode is suitable for all vanadium redox flow batteries, iron-chromium redox flow batteries, all iron redox flow batteries and zinc-based redox flow batteries. The catalytically active component of the alloy catalyst layer with gradient pore structure contains one or more of Ni, Co, Cu, Fe, Bi, In, and Sb. The number of alloy layers is 2 to 5, the thickness of each layer is 0.2 μm to 2 μm, the total thickness of the alloy layers is 0.5 μm to 5 μm, the maximum pore size is 50 nm to 200 nm, and the minimum pore size is 1 nm to 50 nm.

[0018] The design concept of this invention is: This invention creatively combines stepwise electrochemical deposition with dealloying technology. By designing multilayer alloy layers with compositional gradients, and taking advantage of the different dissolution rates caused by the difference in the content of sacrificial components during dealloying, the active components in the alloy layers are selectively dissolved in the corrosive medium, forming a nanoporous structure on the material surface and achieving a gradient change in pore size along the electrode thickness direction.

[0019] In multilayer alloy design, the content of sacrificial components from the inner to the outer layers can be designed to gradually decrease or gradually increase. When the content of sacrificial components gradually decreases from the inner to the outer layers, the outer layer has a low content of sacrificial components, dissolves more slowly during the dealloying process, and forms small pores; the inner layer has a high content of sacrificial components, dissolves more quickly, and forms large pores, thus obtaining a gradient structure with pore size gradually increasing from the surface to the bottom layer. Conversely, when the content of sacrificial components gradually increases from the inner to the outer layers, a gradient structure with pore size gradually decreasing from the surface to the bottom layer can be obtained. This structure is more beneficial for flow battery applications: the large pores on the surface serve as rapid electrolyte transport channels, reducing mass transfer resistance, while the small pores on the bottom layer provide high specific surface area active regions, increasing reactive sites. By controlling the number of layers, layer thickness, and the difference in sacrificial component content between layers, the pore size gradient can be precisely controlled. The more layers and the smaller the difference in content between layers, the more continuous the pore size change; the fewer layers and the larger the difference in content between layers, the more step-like the change is formed. Dealloying conditions (potential, time) can adjust the pore size as a whole, but do not change the gradient trend.

[0020] This gradient pore structure design offers several unique advantages: First, structural gradients can be achieved through simple compositional gradient design, eliminating the need for complex equipment. Second, the gradient pore structure can simultaneously optimize mass transfer and reactivity, enhancing the overall electrode performance. Third, the multilayer alloy design allows for independent control of parameters in each layer, enabling precise design of the pore size gradient. Fourth, this method is applicable to various alloy systems, demonstrating good versatility. This method boasts advantages such as simple processing, low cost, and scalability, significantly enhancing the catalytic activity of redox reactions in flow batteries. It provides a new approach for the fabrication of gradient pore structure electrodes and offers an innovative solution for improving the power density and energy efficiency of flow batteries.

[0021] The advantages and beneficial effects of this invention are as follows: 1. By designing a multi-layer alloy composition gradient, a porous alloy catalyst layer with varying pore size is formed on the surface of the carbon felt by utilizing the difference in dissolution rate during the dealloying process.

[0022] 2. Controllable gradient structure: By adjusting the number of layers (2~5 layers), layer thickness (0.2μm~2μm / layer), and the difference in the content of sacrificial components between layers (10%~50%), the total thickness of the gradient layer (0.5μm~5μm), the maximum pore size (50nm~200nm), and the minimum pore size (1nm~50nm) can be precisely controlled.

[0023] 3. It uses conventional electrochemical deposition and dealloying equipment, eliminating the need for expensive lasers or templates, resulting in low cost and easy mass production.

[0024] 4. Applicable to various alloy systems (Ni-Zn, Co-Zn, Cu-Zn, Ni-Al, etc.), and the appropriate catalytic active metal can be selected according to the needs of different flow battery systems.

[0025] 5. The multilayer alloy forms a good bond with the carbon substrate through stepwise deposition. After dealloying, the gradient pore structure grows in situ, which is not easy to fall off, and the electrode has excellent cycle stability. Attached Figure Description

[0026] Figure 1 The image shows the pore size distribution curve of the composite electrode alloy catalyst layer with gradient pore structure prepared in Example 1. Detailed Implementation

[0027] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. It should be noted that the embodiments described in this invention are only for further explanation and illustration, and not for limiting their application scope. Based on this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention.

[0028] This invention discloses a method for preparing a gradient-pore structure alloy catalyst composite electrode based on electrochemical dealloying. In the specific implementation process, the carbon felt substrate is first pretreated to introduce oxygen-containing functional groups. Then, multiple alloy layers with different sacrificial component contents are deposited sequentially through stepwise electrochemical deposition. Subsequently, a dealloying process is performed to construct a gradient pore structure. Finally, the composite electrode is obtained after cleaning and drying. Specifically, the process includes the following: (1) Substrate pretreatment: The carbon felt is cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then, it is immersed in 5wt%~30wt% HNO3 solution at 60℃~90℃ for 1~6 hours to introduce oxygen-containing functional groups and enhance the bonding force between the subsequent alloy layer and the carbon fiber. Then, it is repeatedly rinsed with deionized water until neutral and dried in a vacuum drying oven at 60℃~100℃ for 6~12 hours for later use.

[0029] (2) Multilayer gradient alloy layer deposition: At least two alloy layers with different sacrificial component contents were sequentially deposited on the surface of the pretreated carbon felt substrate using electrochemical deposition. Electrolytes with different sacrificial component contents were prepared sequentially. The pretreated carbon felt was used as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. The alloy layers were deposited sequentially at a constant potential. During deposition, the total metal ion concentration was 0.05 mol / L to 0.5 mol / L, the deposition potential was -1.5 V to -0.5 V vs. SCE, the deposition time was 5 to 30 minutes, and the deposition temperature was 25℃ to 50℃. After each layer was deposited, it was removed and rinsed with deionized water, but drying was not required before proceeding to the next layer. The total atomic percentage of the catalytically active component in each alloy layer is 20%~80%, the total atomic percentage of the sacrificial component is 20%~80%, the difference in sacrificial component content between adjacent layers is 10%~50%, the number of layers is 2~5, the thickness of each layer is 0.2μm~2μm, and the total thickness of the alloy layer is 0.5μm~5μm.

[0030] (3) Construction of gradient pore structure: Carbon felt coated with multiple gradient alloy layers was placed in an acidic corrosive medium and dealloyed using a constant potential method. Taking advantage of the different dissolution rates caused by the differences in the content of sacrificial components in each layer, the sacrificial components were selectively dissolved, forming a porous alloy catalyst layer structure with gradient pore size along the thickness direction of the carbon felt. The potential range was -0.2V to 0.5V vs. SCE, and the treatment time was 10 to 120 minutes; the acidic corrosive medium was a 0.1 mol / L to 2.0 mol / L H2SO4, HCl, or HNO3 solution. During the treatment, nitrogen gas was introduced for stirring or ultrasonic assistance was applied, with a gas flow rate of 10 mL / min to 100 mL / min and an ultrasonic power of 50 W to 300 W. After dealloying, the layer was removed. The maximum pore size of the alloy layer corresponding to the highest sacrificial component content was 50 nm to 200 nm, and the minimum pore size corresponding to the lowest sacrificial component content was 10 nm to 50 nm.

[0031] (4) Post-treatment: The electrode after the dealloying treatment is rinsed repeatedly with deionized water 3 to 5 times and dried in a vacuum drying oven at 60℃ to 100℃ for 6 to 12 hours to obtain a modified carbon felt electrode with a surface-loaded gradient pore structure alloy catalyst layer.

[0032] The raw materials and equipment used, such as carbon felt of different specifications and metal salts, are all commercially available.

[0033] The present invention will now be described in further detail through embodiments.

[0034] Example 1 Three-layer Ni-Zn gradient porous electrode was prepared (the content of sacrificial component decreased from the inner layer to the outer layer).

[0035] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0036] (2) Three-layer gradient alloy layer deposition: Three Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0037] First (inner) electrolyte: Ni 2+ The concentration is 0.05 mol / L, Zn 2+ The concentration was 0.15 mol / L, the total concentration was 0.2 mol / L, the Zn content was 75%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 10 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30 °C.

[0038] Second (middle) electrolyte: Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L sodium citrate was added. Deposition continued for 15 minutes on top of the first layer.

[0039] Third (outer) electrolyte: Ni 2+ The concentration is 0.15 mol / L, Zn 2+ The concentration was 0.05 mol / L, the total concentration was 0.2 mol / L, the Zn content was 25%, and 0.1 mol / L sodium citrate was added. Deposition continued for 20 minutes on top of the second layer.

[0040] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0041] (3) Gradient pore structure construction: A one-step dealloying process was adopted. The carbon felt coated with three Ni-Zn alloy layers was placed in a 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a constant potential of 0.1 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after the dealloying was completed.

[0042] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-1.

[0043] Modified carbon felt electrode CF-GNi-1: Scanning electron microscopy shows that the cross-section has a distinct gradient pore structure, and the pore size distribution curve is as follows. Figure 1As shown, the total thickness of the gradient layer is approximately 3.5 μm; the specific surface area is increased to 35.5 m². 2 / g, the electrochemical active area increased to 158.6mF / cm 2 Assembled into a single vanadium redox flow battery, achieving a current of 200 mA / cm². 2 The energy efficiency was 86.8% when tested at current density.

[0044] Example 2 Three-layer Ni-Zn gradient porous electrode was prepared (the content of sacrificial component increases from the inner layer to the outer layer).

[0045] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0046] (2) Three-layer gradient alloy layer deposition: Three Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0047] First (inner) electrolyte: Ni 2+ The concentration is 0.15 mol / L, Zn 2+ The concentration was 0.05 mol / L, the total concentration was 0.2 mol / L, the Zn content was 25%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out at -1.2 V vs. SCE potential for 20 minutes at a deposition temperature of 30℃.

[0048] Second (middle) electrolyte: Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L sodium citrate was added. Deposition continued for 15 minutes on top of the first layer.

[0049] Third (outer) electrolyte: Ni 2+ The concentration is 0.05 mol / L, Zn 2+ The concentration was 0.15 mol / L, the total concentration was 0.2 mol / L, the Zn content was 75%, and 0.1 mol / L sodium citrate was added. Deposition continued for 10 minutes on top of the second layer.

[0050] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0051] (3) Construction of gradient pore structure: The carbon felt coated with three Ni-Zn alloy layers was placed in 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at 0.1 V vs. SCE potential using the constant potential method to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after dealloying was completed.

[0052] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-2.

[0053] Modified carbon felt electrode CF-GNi-2: Scanning electron microscopy revealed a distinct gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 3.5 μm; the specific surface area was increased to 34.8 m². 2 / g, the electrochemical active area increased to 152.3mF / cm 2 Assembled into a single all-ferric flow battery, at 80 mA / cm². 2 The energy efficiency was 74.5% when tested at current density.

[0054] Example 3 Two-layer Ni-Zn gradient hole electrodes were prepared (the content of sacrificial components decreased from the inner layer to the outer layer).

[0055] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0056] (2) Deposition of two gradient alloy layers: Two Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0057] First (inner) electrolyte: Ni 2+ The concentration is 0.05 mol / L, Zn 2+ The concentration was 0.15 mol / L, the total concentration was 0.2 mol / L, the Zn content was 75%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 20 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30 °C.

[0058] Second (outer) electrolyte: Ni 2+ The concentration is 0.15 mol / L, Zn 2+ The concentration was 0.05 mol / L, the total concentration was 0.2 mol / L, the Zn content was 25%, and 0.1 mol / L sodium citrate was added. Deposition continued for 20 minutes on top of the first layer.

[0059] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0060] (3) Construction of gradient pore structure: The carbon felt coated with two Ni-Zn alloy layers was placed in 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a constant potential of 0.1 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The carbon felt was removed after dealloying was completed.

[0061] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-3.

[0062] Modified carbon felt electrode CF-GNi-3: Scanning electron microscopy reveals a stepped gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 3.2 μm; the specific surface area is increased to 30.2 m². 2 / g, the electrochemical active area increased to 138.5mF / cm 2 Assembled into a single vanadium redox flow battery, achieving a current of 200 mA / cm². 2 The energy efficiency was 85.5% when tested at current density.

[0063] Example 4 A four-layer Ni-Zn gradient hole electrode was fabricated (the content of the sacrificial component decreased from the inner layer to the outer layer).

[0064] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0065] (2) Four-layer gradient alloy layer deposition: Four Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0066] First (innermost) electrolyte layer: Ni 2+ The concentration is 0.04 mol / L, Zn 2+ The concentration was 0.16 mol / L, the total concentration was 0.2 mol / L, the Zn content was 80%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 8 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30 °C.

[0067] Second electrolyte layer: Ni 2+ The concentration is 0.08 mol / L, Zn 2+The concentration was 0.12 mol / L, the total concentration was 0.2 mol / L, the Zn content was 60%, and 0.1 mol / L sodium citrate was added. Deposition continued for 10 minutes on top of the first layer.

[0068] Third electrolyte layer: Ni 2+ The concentration is 0.12 mol / L, Zn 2+ The concentration was 0.08 mol / L, the total concentration was 0.2 mol / L, the Zn content was 40%, and 0.1 mol / L sodium citrate was added. Deposition continued for 12 minutes on top of the second layer.

[0069] Fourth (outermost) electrolyte: Ni 2+ The concentration is 0.16 mol / L, Zn 2+ The concentration was 0.04 mol / L, the total concentration was 0.2 mol / L, the Zn content was 20%, and 0.1 mol / L sodium citrate was added. Deposition continued for 15 minutes on top of the third layer.

[0070] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0071] (3) Construction of gradient pore structure: The carbon felt coated with four Ni-Zn alloy layers was placed in 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a constant potential of 0.1 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The carbon felt was removed after dealloying was completed.

[0072] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-4.

[0073] Modified carbon felt electrode CF-GNi-4: Scanning electron microscopy reveals a continuous gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 4.2 μm; the specific surface area is increased to 38.5 m². 2 / g, the electrochemical active area increased to 168.5mF / cm 2 Assembled into a single vanadium redox flow battery, achieving a current of 220 mA / cm². 2 The energy efficiency was 88.5% when tested at current density.

[0074] Example 5 The dealloying time differs from that of Example 1 (30 minutes).

[0075] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0076] (2) Three-layer gradient alloy layer deposition: Three Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0077] First (inner) electrolyte: Ni 2+ The concentration is 0.05 mol / L, Zn 2+ The concentration was 0.15 mol / L, the total concentration was 0.2 mol / L, the Zn content was 75%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 10 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30 °C.

[0078] Second (middle) electrolyte: Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L sodium citrate was added. Deposition continued for 15 minutes on top of the first layer.

[0079] Third (outer) electrolyte: Ni 2+ The concentration is 0.15 mol / L, Zn 2+ The concentration was 0.05 mol / L, the total concentration was 0.2 mol / L, the Zn content was 25%, and 0.1 mol / L sodium citrate was added. Deposition continued for 20 minutes on top of the second layer.

[0080] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0081] (3) Construction of gradient pore structure: The carbon felt coated with three Ni-Zn alloy layers was placed in 0.5 mol / L H2SO4 solution and dealloyed for 30 minutes at a constant potential of 0.1 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The carbon felt was removed after dealloying was completed.

[0082] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-5.

[0083] Modified carbon felt electrode CF-GNi-5: Scanning electron microscopy reveals a gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 3.5 μm; the specific surface area is increased to 28.5 m².2 / g, the electrochemical active area increased to 128.5mF / cm². 2 Assembled into a single vanadium redox flow battery, achieving a current of 250 mA / cm². 2 The energy efficiency was 84.5% when tested at current density.

[0084] Example 6 The dealloying time differs from that of Example 1 (90 minutes).

[0085] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0086] (2) Three-layer gradient alloy layer deposition: Three Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0087] First (inner) electrolyte: Ni 2+ The concentration is 0.05 mol / L, Zn 2+ The concentration was 0.15 mol / L, the total concentration was 0.2 mol / L, the Zn content was 75%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 10 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30 °C.

[0088] Second (middle) electrolyte: Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L sodium citrate was added. Deposition continued for 15 minutes on top of the first layer.

[0089] Third (outer) electrolyte: Ni 2+ The concentration is 0.15 mol / L, Zn 2+ The concentration was 0.05 mol / L, the total concentration was 0.2 mol / L, the Zn content was 25%, and 0.1 mol / L sodium citrate was added. Deposition continued for 20 minutes on top of the second layer.

[0090] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0091] (3) Construction of gradient pore structure: The carbon felt coated with three Ni-Zn alloy layers was placed in 0.5 mol / L H2SO4 solution and dealloyed for 90 minutes at 0.1 V vs. SCE potential using the constant potential method to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after dealloying was completed.

[0092] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-6.

[0093] Modified carbon felt electrode CF-GNi-6: Scanning electron microscopy reveals a gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 3.5 μm; the specific surface area is increased to 36.5 m². 2 / g, the electrochemical active area increased to 162.5mF / cm². 2 Assembled into a single vanadium redox flow battery, achieving a current of 200 mA / cm². 2 The energy efficiency was 87.5% when tested at current density.

[0094] Example 7 The dealloying potential is different from that in Example 1 (0.2 V).

[0095] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0096] (2) Three-layer gradient alloy layer deposition: Three Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0097] First (inner) electrolyte: Ni 2+ The concentration is 0.05 mol / L, Zn 2+ The concentration was 0.15 mol / L, the total concentration was 0.2 mol / L, the Zn content was 75%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 10 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30°C.

[0098] Second (middle) electrolyte: Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L sodium citrate was added. Deposition continued for 15 minutes on top of the first layer.

[0099] Third (outer) electrolyte: Ni 2+ The concentration is 0.15 mol / L, Zn 2+ The concentration was 0.05 mol / L, the total concentration was 0.2 mol / L, the Zn content was 25%, and 0.1 mol / L sodium citrate was added. Deposition continued for 20 minutes on top of the second layer.

[0100] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0101] (3) Construction of gradient pore structure: The carbon felt coated with three Ni-Zn alloy layers was placed in 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at 0.2 V vs. SCE potential using the constant potential method to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after dealloying was completed.

[0102] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-7.

[0103] Modified carbon felt electrode CF-GNi-7: Scanning electron microscopy reveals a gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 3.5 μm; the specific surface area is increased to 37.2 m². 2 / g, the electrochemical active area increased to 165.8mF / cm 2 Assembled into a single all-ferric flow battery, at 70 mA / cm². 2 The energy efficiency was 87.8% when tested at current density.

[0104] Example 8 Three-layer Co-Zn gradient porous electrode was prepared (the content of sacrificial component decreased from the inner layer to the outer layer).

[0105] (1) Substrate pretreatment: The polyacrylonitrile-based carbon felt was cut into 10cm x 10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0106] (2) Three-layer gradient alloy layer deposition: Three Co-Zn alloy electrolytes with different Zn contents were prepared.

[0107] First layer (inner layer) electrolyte: Co 2+ The concentration is 0.05 mol / L, Zn 2+The concentration was 0.15 mol / L, the total concentration was 0.2 mol / L, the Zn content was 75%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 10 minutes at -1.1 V vs. SCE potential at a deposition temperature of 30 °C.

[0108] Second (middle) electrolyte: Co 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L sodium citrate was added. Deposition continued for 15 minutes on top of the first layer.

[0109] Third (outer) electrolyte: Co 2+ The concentration is 0.15 mol / L, Zn 2+ The concentration was 0.05 mol / L, the total concentration was 0.2 mol / L, the Zn content was 25%, and 0.1 mol / L sodium citrate was added. Deposition continued for 20 minutes on top of the second layer.

[0110] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0111] (3) Construction of gradient pore structure: The carbon felt coated with three layers of Co-Zn alloy was placed in 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at 0.1 V vs. SCE potential using the constant potential method to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after dealloying was completed.

[0112] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GCo-8.

[0113] Modified carbon felt electrode CF-GCo-8: Scanning electron microscopy reveals a distinct gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 3.5 μm; the specific surface area is increased to 32.5 m². 2 / g, the electrochemical active area increased to 142.5mF / cm². 2 Assembled into a single all-ferric flow battery, at 80 mA / cm². 2 The energy efficiency was 85.8% when tested at current density.

[0114] Example 9 Three-layer Cu-Zn gradient porous electrode was prepared (the content of sacrificial component decreased from the inner layer to the outer layer).

[0115] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0116] (2) Three-layer gradient alloy layer deposition: Three Cu-Zn alloy electrolytes with different Zn contents were prepared.

[0117] First (inner) electrolyte layer: Cu 2+ The concentration is 0.05 mol / L, Zn 2+ The concentration was 0.15 mol / L, the total concentration was 0.2 mol / L, the Zn content was 75%, and 0.1 mol / L potassium sodium tartrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 8 minutes at -0.9 V vs. SCE potential at a deposition temperature of 30 °C.

[0118] Second (middle) electrolyte: Cu 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L potassium sodium tartrate was added. Deposition continued for 12 minutes on top of the first layer.

[0119] Third (outer) electrolyte: Cu 2+ The concentration is 0.15 mol / L, Zn 2+ The concentration was 0.05 mol / L, the total concentration was 0.2 mol / L, the Zn content was 25%, and 0.1 mol / L potassium sodium tartrate was added. Deposition continued for 16 minutes on top of the second layer.

[0120] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0121] (3) Construction of gradient pore structure: The carbon felt coated with three Cu-Zn alloy layers was placed in 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a constant potential of 0.1 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The carbon felt was removed after dealloying was completed.

[0122] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GCu-9.

[0123] Modified carbon felt electrode CF-GCu-9: Scanning electron microscopy reveals a distinct gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 3.2 μm; the specific surface area is increased to 30.5 m².2 / g, the electrochemical active area increased to 135.8mF / cm 2 Assembled into a single zinc-bromine flow battery, at 60 mA / cm². 2 The energy efficiency was 84.8% when tested at current density.

[0124] Example 10 The difference in the content of sacrificial components between adjacent layers is different from that in Example 1 (15%).

[0125] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0126] (2) Three-layer gradient alloy layer deposition: Three Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0127] First (inner) electrolyte: Ni 2+ The concentration is 0.07 mol / L, Zn 2+ The concentration was 0.13 mol / L, the total concentration was 0.2 mol / L, the Zn content was 65%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 12 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30 °C.

[0128] Second (middle) electrolyte: Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L sodium citrate was added. Deposition continued for 15 minutes on top of the first layer.

[0129] Third (outer) electrolyte: Ni 2+ The concentration is 0.13 mol / L, Zn 2+ The concentration was 0.07 mol / L, the total concentration was 0.2 mol / L, the Zn content was 35%, and 0.1 mol / L sodium citrate was added. Deposition continued for 18 minutes on top of the second layer.

[0130] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0131] (3) Construction of gradient pore structure: The carbon felt coated with three Ni-Zn alloy layers was placed in 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at 0.1 V vs. SCE potential using the constant potential method to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after dealloying was completed.

[0132] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-10.

[0133] Modified carbon felt electrode CF-GNi-10: Scanning electron microscopy reveals a gently sloping gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 3.8 μm; the specific surface area is increased to 33.5 m². 2 / g, the electrochemical active area increased to 148.5mF / cm 2 Assembled into a single zinc-bromine flow battery, at 75 mA / cm². 2 The energy efficiency was 86.5% when tested at current density.

[0134] Example 11 Unlike the one-step dealloying in Example 1, this example uses a step-by-step dealloying process.

[0135] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0136] (2) Three-layer gradient alloy layer deposition: Three Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0137] First (inner) electrolyte: Ni 2+ The concentration is 0.05 mol / L, Zn 2+ The concentration was 0.15 mol / L, the total concentration was 0.2 mol / L, the Zn content was 75%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 10 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30 °C.

[0138] Second (middle) electrolyte: Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L sodium citrate was added. Deposition continued for 15 minutes on top of the first layer.

[0139] Third (outer) electrolyte: Ni 2+ The concentration is 0.15 mol / L, Zn 2+ The concentration was 0.05 mol / L, the total concentration was 0.2 mol / L, the Zn content was 25%, and 0.1 mol / L sodium citrate was added. Deposition continued for 20 minutes on top of the second layer.

[0140] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0141] (3) Gradient pore structure construction: A stepwise dealloying process was adopted. The carbon felt coated with three Ni-Zn alloy layers was placed in a 0.5 mol / L H2SO4 solution and treated for 20 minutes at a potential of 0.05 V vs. SCE, then for 20 minutes at a potential of 0.1 V vs. SCE, and finally for 20 minutes at a potential of 0.15 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process, and the carbon felt was removed after dealloying was completed.

[0142] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-11.

[0143] Modified carbon felt electrode CF-GNi-11: Scanning electron microscopy reveals a distinct gradient pore structure in its cross-section, with a total gradient layer thickness of approximately 3.5 μm; the specific surface area is increased to 39.5 m². 2 / g, the electrochemical active area increased to 178.5mF / cm 2 Assembled into a single vanadium redox flow battery, achieving a current of 200 mA / cm². 2 The energy efficiency was 88.8% when tested at current density.

[0144] Example 12 Five-layer Ni-Zn gradient hole electrode was prepared (the content of sacrificial component decreased from the inner layer to the outer layer).

[0145] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.

[0146] (2) Deposition of five gradient alloy layers: Five Ni-Zn alloy electrolytes with different Zn contents were prepared.

[0147] First (innermost) electrolyte layer: Ni 2+ The concentration is 0.04 mol / L, Zn2+ The concentration was 0.16 mol / L, the total concentration was 0.2 mol / L, the Zn content was 80%, and 0.1 mol / L sodium citrate was added as a complexing agent. Pretreated carbon felt was used as the working electrode, and deposition was carried out for 5 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30℃.

[0148] Second electrolyte layer: Ni 2+ The concentration is 0.07 mol / L, Zn 2+ The concentration was 0.13 mol / L, the total concentration was 0.2 mol / L, the Zn content was 65%, and 0.1 mol / L sodium citrate was added. Deposition continued for 7 minutes on top of the first layer.

[0149] Third electrolyte layer: Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, the Zn content was 50%, and 0.1 mol / L sodium citrate was added. Deposition continued for 9 minutes on top of the second layer.

[0150] Fourth electrolyte layer: Ni 2+ The concentration is 0.13 mol / L, Zn 2+ The concentration was 0.07 mol / L, the total concentration was 0.2 mol / L, the Zn content was 35%, and 0.1 mol / L sodium citrate was added. Deposition continued for 11 minutes on top of the third layer.

[0151] Fifth (outermost) electrolyte: Ni 2+ The concentration is 0.16 mol / L, Zn 2+ The concentration was 0.04 mol / L, the total concentration was 0.2 mol / L, the Zn content was 20%, and 0.1 mol / L sodium citrate was added. Deposition continued for 13 minutes on top of the fourth layer.

[0152] After deposition, remove the material, rinse with deionized water, and dry at room temperature.

[0153] (3) Construction of gradient pore structure: The carbon felt coated with five Ni-Zn alloy layers was placed in 0.5 mol / L H2SO4 solution and dealloyed for 60 minutes at a constant potential of 0.1 V vs. SCE to selectively dissolve Zn. Nitrogen gas was introduced and stirred during the process. The carbon felt was removed after dealloying was completed.

[0154] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt electrode CF-GNi-12.

[0155] Modified carbon felt electrode CF-GNi-12: Scanning electron microscopy reveals a continuous and smooth gradient pore structure in the cross-section, with a total gradient layer thickness of approximately 4.8 μm; the specific surface area is increased to 42.5 m². 2 / g, the electrochemical active area increased to 175.5mF / cm 2 Assembled into a single iron-chromium redox flow battery, at 70 mA / cm². 2 The energy efficiency was 79.5% when tested at current density.

[0156] The results of the examples demonstrate that the stepwise electrochemical deposition combined with dealloying method of the present invention can successfully construct a porous alloy catalyst layer with gradient pore size on the surface of a carbon felt electrode through a simple and controllable process. The continuity of the gradient change can be controlled by adjusting the number of layers; the pore size gradient can be controlled by adjusting the difference in the content of sacrificial components between layers; the thickness of each layer and the total thickness of the gradient layer can be controlled by adjusting the deposition time; the overall pore size can be controlled by adjusting the dealloying time and potential; the uniformity and hierarchy of the gradient structure can be further optimized by ultrasonic-assisted or stepwise dealloying; and different application requirements can be met by selecting different alloy systems and sacrificial components. The prepared gradient pore structure composite electrode provides a rapid mass transfer channel in the surface pores and a high specific surface area active region in the bottom pores, with the synergistic effect increasing the electrode's specific surface area to 25 μm². 2 / g~42m 2 / g, the electrochemical active area is increased to 120mF / cm 2 ~185mF / cm 2 This electrode, through its inherent gradient pore structure design, effectively coordinates the multiple requirements of flow battery electrodes for efficient mass transfer and high reactivity, providing a key electrode material solution for the development of next-generation high-performance, high-power-density flow batteries.

Claims

1. A method for preparing a gradient-pore structure alloy catalyst composite electrode based on electrochemical dealloying, characterized in that, Includes the following: The carbon felt substrate is first acid-treated to introduce oxygen-containing functional groups, and then at least two alloy layers are sequentially deposited on the surface. Each alloy layer contains catalytically active components and sacrificial components, and the content of sacrificial components in each alloy layer is different. Then, a dealloying process is performed to remove the sacrificial components in each alloy layer, thereby forming an alloy catalyst layer with a gradient pore structure in situ along the thickness direction on the surface of the carbon felt substrate, resulting in a composite electrode with an alloy catalyst layer with a gradient pore structure on the surface.

2. The method for preparing a gradient-pore structure alloy catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The carbon felt substrate includes polyacrylonitrile-based carbon felt, pitch-based graphite felt, adhesive-based carbon felt, or carbon paper. The acid treatment includes the following steps: the carbon felt substrate is ultrasonically degreased in acetone, ethanol, and deionized water for 10-30 minutes in sequence, then soaked in 5wt%-30wt% HNO3 or H2SO4 solution at 60℃-90℃ for 1-6 hours to introduce oxygen-containing functional groups, washed with deionized water until neutral, and then dried at 60℃-100℃ for 6-12 hours.

3. The method for preparing a gradient-pore structure alloy catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, Methods for depositing alloy layers include the following: At least two alloy layers are sequentially deposited on the surface of a carbon felt substrate using a stepwise electrochemical deposition method. The catalytic active components of each alloy layer are independently selected from one or more of Ni, Co, Cu, Fe, Bi, In, and Sb; the sacrificial components of each alloy layer are independently selected from one or more of Zn, Al, and Mg.

4. The method for preparing a gradient-pore structure alloy catalyst composite electrode based on electrochemical dealloying according to claim 3, characterized in that, When depositing each alloy layer, the electrolyte is a metal ion salt solution containing catalytically active components and sacrificial components, with a total metal ion concentration of 0.05 mol / L to 0.5 mol / L, a deposition potential of -1.5 V to -0.5 V, a deposition time of 5 to 30 minutes, and a deposition temperature of 25℃ to 50℃.

5. The method for preparing a gradient-pore structure alloy catalyst composite electrode based on electrochemical dealloying according to claim 3, characterized in that, In each alloy layer, the total atomic percentage of the catalytically active component is 20%~80%, and the total atomic percentage of the sacrificial component is 20%~80%. From the innermost layer to the outermost layer, the content of the sacrificial component decreases or increases layer by layer, and the difference in the content of the sacrificial component between adjacent layers is 10%~50%.

6. The method for preparing a gradient-pore structure alloy catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The dealloying process includes the following: An electrochemical method is used to selectively dissolve sacrificial components in each alloy layer in an acidic medium through one-step or stepwise dealloying, forming a gradient pore structure.

7. The method for preparing a gradient-pore structure alloy catalyst composite electrode based on electrochemical dealloying according to claim 6, characterized in that, Dealloying is performed using either a constant potential method or a constant current method. The constant potential method has a potential range of -0.2V to 0.5V and a processing time of 10 to 120 minutes; the constant current method uses a current density of 1 mA / cm². 2 ~20mA / cm 2 The treatment time is 10~120 minutes; the acidic medium is a 0.1mol / L~2.0mol / L H2SO4, HCl or HNO3 solution.

8. The method for preparing a gradient-pore structure alloy catalyst composite electrode based on electrochemical dealloying according to claim 6, characterized in that, During the dealloying process, an inert gas is introduced for stirring or ultrasonic assistance is provided. The gas flow rate is 10 mL / min to 100 mL / min, and the ultrasonic power is 50 W to 300 W. After the dealloying treatment, the electrode is rinsed repeatedly with deionized water or ethanol 3 to 5 times and dried at 60℃ to 100℃ for 6 to 12 hours to obtain a composite electrode with an alloy catalyst layer with a gradient pore structure on the surface.

9. The composite electrode obtained by the method for preparing a gradient pore structure alloy catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The composite electrode is used as a flow battery electrode and is suitable for all-vanadium redox flow batteries, iron-chromium redox flow batteries, all-iron redox flow batteries, and zinc-based redox flow batteries. The alloy catalyst layer has a gradient pore structure, and the catalytic active component contains one or more of Ni, Co, Cu, Fe, Bi, In, and Sb. The number of alloy layers is 2 to 5, the thickness of each layer is 0.2 μm to 2 μm, the total thickness of the alloy layers is 0.5 μm to 5 μm, the maximum pore size is 50 nm to 200 nm, and the minimum pore size is 1 nm to 50 nm.